Efficacy of empiric esophageal dilation in patients with non-obstructive dysphagia: systematic review and meta-analysis. (2nd December 2021) - Kamal, Faisal; Khan, Muhammad Ali; Lee-Smith, Wade; Sharma, Sachit; Jowhar, Dawit; Farooq, Umer; Acharya, Ashu; Kouanda, Abdul; Imam, Zaid; Ahmed, Nazneen; Henry, Collin; Saleem, Nasir; et al.
Abstract: Background and aims: Empiric esophageal dilation is frequently performed for non-obstructive dysphagia. Studies evaluating its efficacy have reported conflicting results. In this meta-analysis, we have evaluated the efficacy of esophageal dilation in the management of non-obstructive dysphagia. Methods: We reviewed several databases from inception to 26 May 2021 to identify randomized controlled trials (RCTs) and observational studies that evaluated the role of empiric esophageal dilation for non-obstructive dysphagia. Our outcomes of interest were clinical success (improvement in dysphagia after dilation) and difference in post-operative dysphagia score between groups. For categorical variables, we calculated pooled odds ratios (OR) with 95% confidence intervals (CI); for continuous variables, we calculated standardized mean difference (SMD) with 95% CI. Data were analyzed using a random effects model. We used GRADE framework to ascertain the quality of evidence. Results: We included 4 studies (3 RCTs and one observational) with 243 patients; there were 133 treated with empiric dilation and 110 controls. We found no significant difference in clinical success (OR (95% CI) 1.91 (0.89, 4.08)) or post-procedure dysphagia score between groups (SMD (95% CI) 0.38 (−0.37, 1.14)). Our findings remained consistent on subgroup analysis including RCTs only. Quality of evidence ranged from low to very low based on GRADE framework. Conclusions: Our meta-analysis does not support the use of empiric esophageal dilation in patients with non-obstructive dysphagia. More studies are required to confirm these findings.